A new record and redescription of Baetis (Rhodobaetis) oreophilus Kluge, 1982 (Baetidae: Ephemeroptera) from the north-western Himalaya - Vasanth, M.; Paray, N.a.; Kubendran, T.; Subramanian, K.a. (Zootaxa, 2026)
A new record of the species Baetis (Rhodobaetis) oreophilus Kluge, 1982 is based on larvae collected from Lam stream, Pulwama district, Jammu & Kashmir. The species is reported for the first time from India, and re-described after four decades based on larval material. It is placed within the subgenus Rhodobaetis s.l. Jacob, 2003. A comparison table between closely related species of the subgenus and distribution map is also provided.